Analisis Kadar Air dan Total Petroleum Hydrocarbon (TPH) dari Proses Bioremediasi Limbah Oli dengan Metode Pengomposan - Husnawati Yahya (Jurnal Serambi Engineering, 2019)
Engine oil waste is a pollutant that causes environmental pollution and risk for human health. Bioremediation is one of the solutions to solve this problem. In this research, engine oil waste was remediation by composting method. The composting process was conducted in Environmental Engineering laboratory for 35 days.  Water Content and total petroleum  hydrocarbon (TPH) was analyzed in Chemical Engineering laboratory to show the degrada-tion of engine oil waste by combining of liquid fertilizer and compost. The result showed that Total Petroleum Hydrocarbon (TPH) of engine oil waste degradation reached 81% in sample 8 (by combined 8 mL of liquid or-ganic fertilizer and 300 g of compost soil). Sample 12 (by combined 2 mL of liquid organic fertilizer and 500 g of compost soil) also showed the same result